Representation of the panji figure as a millennial-era avenger - Sari, Ayu Titis Rukmana; Wahyudi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
The purpose of this research is to explore how the character of Panji is represented in the millennial era. The Panji stories are a treasured historical legacy that once flourished in the past, particularly during the Majapahit era, and spread to various regions in the archipelago and some Southeast Asian countries. Panji is closely associated with being a protagonist figure, which is why he is considered a role model for living a righteous life. In the realm of education, the Panji stories can be thoughtfully incorporated as teaching materials for students, particularly in character education.The character of Panji can serve as a model or avenger, akin to a Nusantara superhero. This research adopts a qualitative research method, and data is collected through secondary sources, such as literature, books, articles, documents, and websites. The findings of this research represent Panji as an avenger in the millennial era, combating the growing influence of Western culture that has seeped into the paradigm of the millennial generation in Indonesia. Moreover, it fosters a sense of patriotism by appreciating the rich cultural heritage of the nation.